Estimating discharge in ungauged catchment of Sungai Muar - Muslim, Muhammad (2016)
River discharge is one of the most important parameters in river basins study to forecast drought or flood events from a time-series of stream flow and rainfall runoff. Unfortunately in Malaysia, the existing discharge stations are limited and cater only small parts a basin. This study aims to estimate the discharge in ungauged catchment of Sungai Muar, using HEC-HMS hydrological modelling software. In this study, maps and hydrological data were collected from SRTM and DID, and the data were pre-analyzed for modelling data input. Clark Unit Hydrograph method was used HEC-HMS to simulate the daily stream flow through calibration against available gauged data. From the result obtained, Clark Unit hydrograph method is applicable in estimating flow discharge in ungauged Muar catchment through projection of calibration discharge -simulation based one available data. The results indicate that this hydrological scheme that has been developed is good in simulating hydrograph for low flow period but a little weaker for high flow period as Root Mean Square error value for low flow 11.46 m3/s smaller than high flow simulation 18.45 m3/s. While Nash-Sutcliffe Efficiency for the low flow value is 0.23 bigger than high flow simulation value 0.017. From these two error analysis, it is proven that low flow simulation is more accurate compare to high flow simulation.